Heterozygous carriers of Nijmegen Breakage Syndrome have a distinct gene expression phenotype - Cheung, Vivian G.; Ewens, Warren J.

(untitled) (Genome Research, 2006)
Autosomal recessive diseases are those that require mutations in both alleles to exhibit the disorder. Although most recessive conditions are rare, heterozygous carriers of recessive mutations are quite common. In this study, we show that carriers of Nijmegen Breakage Syndrome (NBS) have a distinct gene expression phenotype that differs from that of noncarriers and also from that of carriers of a similar syndrome, Ataxia Telangiectasia (AT). We found 520 genes whose expression levels differ significantly (P ≤ 0.001) between NBS carriers and controls. By linear discriminant analysis, we found a combination of 16 genes that allows 100% correct classification of individuals as either NBS carriers or noncarriers in a training set with 25 individuals, and in a test set with 52 individuals. When applied to AT carriers, the discriminant function misclassified only one out of 18 AT carriers as an NBS carrier. Our result shows that NBS carriers have a specific gene expression phenotype. It suggests that heterozygous mutations can contribute significantly to natural variation in gene expression. This has implications for the role that heterozygosity for recessive diseases plays in the overall genetic architecture of complex human traits and diseases.